Back analysis of rock mass parameters and initial stress for the Longtan tunnel in China. (July 2016) - Gao, Wei; Ge, Mingming
Abstract The Longtan tunnel is one key tunnel along the Hurong (Shanghai–Chengdu) national roadway in the Hubei province of China. This tunnel is a typical long and deep tunnel, with a length of approximately 8700 m and a depth of approximately 500 m. Because of the complicated geological conditions and high initial stress, to compute the stability of the surrounding rock, it is very important to back analyze the material parameters and initial stress from the measured displacements. Based on a novel evolutionary neural network proposed by the author, a new back analysis method is proposed that can be used to simultaneously determine the material parameters and the initial stress. Using this new back analysis method, some typical monitoring sections of the Longtan tunnel are computed. From numerical computations using the back analysis results, it is found that the stability of the tunnel is consistent with engineering practice and that the initial stresses determined from the back analysis coincide very well with the measured values. Therefore, using the proposed back analysis method, the relevant parameters for the entire tunnel can be conveniently obtained.